Gladiolus - Stevens, Susan; Stevens, Alan B.; Gast, Karen L. B.; O'Mara, Judith A.; Tisserat, Ned A.; Bauernfeind, Robert (My University, 1993)
This publication is for commercial specialty cut flower production specifically gladiolus.
MF1080_1993_08
Keywords: MF1080; Horticulture; Economics; Equipment and Structures; MF